CULTURE, LITERATURE, AND RELIGIOUS RADICALISM IN INDONESIAN SOCIAL MEDIA FROM ACADEMIC WRITING’S POINT OF VIEW - Junaedi Setiyono; Bagiya Bagiya (p-ISSN 2356-0576, 2022)
Abstrac : Art and cultural activities and the attempt to prevent religious radicalism constitute two entities which are considered to have a close relationship. Nowadays, the attempt to prevent religious extremity is crucial to hold, especially in Indonesia. This research aims at interpreting the thesis of texts or essays found in social media online by using the keywords of religion, culture, literature, radicalism, and extremity. Data is collected by finding and collecting essays found in social media dated from 2017 to 2020 by using such keywords. The research is categorized descriptive-qualitative research. In analyzing the data, the theory of developing a thesis proposed by Rodburg and the tutors of the Writing Center at Harvard University is used. There were ten essays found which consisted of 214 to 1088 words. The research findings showed that 60% of the theses found in the ten essays constituted of fact, and 40% of them constituted of opinion. Thus, the thesis of these essays cannot be considered representative thesis because the effective one should constitute argument rather than fact or opinion. The finding also showed that all thesis stated clearly that the relationship between literature or cultural activities and religion was positive. It means that literature or cultural activities is capable of preventing people from religious radicalism or extremity. Keywords: social media, literature, culture, thesis, religion, radicalism, extremity